Pericardium Plug in the Repair of the Corneoscleral Fistula After Ahmed Glaucoma Valve Explantation - Yoo, Chungkwon; Kwon, Sung Wook; Kim, Yong Yeon (Korean journal of ophthalmology, 2008)
We report four cases in which a pericardium (Tutoplast) plug was used to repair a corneoscleral fistula after Ahmed Glaucoma Valve (AGV) explantation. In four cases in which the AGV tube had been exposed, AGV explantation was performed using a pericardium (Tutoplast) plug to seal the defect previously occupied by the tube. After debridement of the fistula, a piece of processed pericardium (Tutoplast), measured 1 mm in width, was plugged into the fistula and secured with two interrupted 10-0 nylon sutures. To control intraocular pressure, a new AGV was implanted elsewhere in case 1, phaco-trabeculectomy was performed concurrently in case 2, cyclophotocoagulation was performed postoperatively in case 3 and anti-glaucomatous medication was added in case 4. No complication related to the fistula developed at the latest follow-up (range: 12-26 months). The pericardium (Tutoplast) plug seems to be an effective method in the repair of corneoscleral fistulas resulting from explantation of glaucoma drainage implants.